One-Pot Thiourea Formation–Palladium-Catalyzed Cyclization Sequence to 3,4-Dihydro-2H-1,3-benzothiazine-2-imines from 2-Halo N-Methylbenzylamine – Scope and Limitations - Lach, Franck (Synlett, 2012)
A practical synthesis of 3,4-dihydro-3-methyl-2H-1,3-benzothiazine-2-imine via intramolecular palladium-catalyzed C–S bond formation is presented and exemplified for both alkyl- and arylisothiocyanates.
Keywords: palladium; heterocycles; sulfur; ring closure; catalysis